Reconsidering adjuvant versus salvage radiation therapy for prostate cancer in the genomics era. (July 2016) - Lobo, Jennifer M; Stukenborg, George J; Trifiletti, Daniel M; Patel, Nirav; Showalter, Timothy N
Aim: We developed a decision analysis framework to simulate the clinical choice of early adjuvant versus delayed salvage radiation therapy after radical prostatectomy.Materials & methods: We designed a Markov decision analysis model to represent two alternative treatment approaches for prostate cancer after prostatectomy over a 10-year time horizon. The model contained individualized inputs including genomic classifier score. Sensitivity analyses were performed to evaluate model results.Results: Observation with delayed salvage radiation is preferred according to the base case, with greater average length and quality of life. However, adjuvant therapy is preferred over observation with salvage when genomics-based estimates of recurrence are high.Conclusion: Model results were sensitive to genomics-based estimates of cancer recurrence and to nonprostate cancer mortality.